Synthesis and structural analysis of ludwigite Co2InBO5 - Zavala, Augurio (2023)
We report the study on the synthesis of indium-doped cobalt ludwigite (Co2InBO5). The Match program, applied to the XRD powder standard, determined that the compound consists of two phases: phase I, ludwigite Co2InBO5 and phase II, the indium oxide In2O3 impurity. The Rietveld refinement applied to the XRD powder standard determined that the percentage by weight of phase I was 98.18% and the percentage by weight of phase II was 1.82%. The atomic ratio between Co and in corresponded to Co/In=2/1, for a goodness of fit s = 1.64 and Chi2 ≅ 2.70. With these adjustment values, the chemical content of the experimental compound was adjusted to its theoretical chemical stoichiometric content. In the unit cell, the different types of atoms occupied the Wyckoff positions 2b, 2c, 4g, and 4h. Atoms of the same or different types can occupy the same Wyckoff position, but a group of them occupy equivalent positions forming a crystallographic orbit. The refined position of each of the different types of atoms, in the unit cell, showed that the B ions, Co and In, form bonds with oxygen generating structural units in the form of triangles (BO3) and in the form of octahedrons (CoO6, InO6). These structural units form low- dimensional substructures such as three-legged ladders 313, 424 and zigzag-shaped planes. Both, the three-legged ladders and the zigzag-shaped planes are formed by the (Co/In)O6 octahedrons, and extend along the crystallographic axis c. These substructures are responsible for their extraordinary physical properties.